2004
DOI: 10.1007/s11248-004-2737-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human erythropoietin (EPO) affects plant morphologies: retarded vegetative growth in tobacco and male sterility in tobacco and Arabidopsis

Abstract: Erythropoietin (EPO) is a glycoprotein used for curing human anemia by regulating the differentiation of erythroid progenitors and the production of red blood cells. To examine the expression of recombinant EPO in plants, pPEV-EP21, in which human epo cDNA under the control of the CaMV 35S promoter, was introduced into tobacco and Arabidopsis via Agrobacterium tumefaciens-mediated transformation. The RNA expression level of epo in the transgenic lines was initially estimated by Northern blot analysis. Two tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 36 publications
(29 reference statements)
5
52
2
Order By: Relevance
“…Among other tested approaches, the codon optimization provided no benefit, EPO native signal peptide was processed more efficiently compared with tobacco signal peptide, and glycosylation was very important for EPO stability in plant tissue. Contrary to our findings with LicKM fusion, others reported that fusion to the elastin-like polypeptide (ELP) carrier protein had a negligible effect on EPO accumulation, which the authors explain by a potential toxicity of the EPO-ELP fusion to the plant [76,79]. This finding is also in contradiction with the potent enhancing effect of fusion to ELP on the expression of human IL-10 and murine IL-4 [80], spider silk protein [80,81], full-size anti-HIV-1 antibody 2F5 [82] in tobacco leaves, and single-chain variable The average of four determinations is shown.…”
Section: Fig 11contrasting
confidence: 99%
See 1 more Smart Citation
“…Among other tested approaches, the codon optimization provided no benefit, EPO native signal peptide was processed more efficiently compared with tobacco signal peptide, and glycosylation was very important for EPO stability in plant tissue. Contrary to our findings with LicKM fusion, others reported that fusion to the elastin-like polypeptide (ELP) carrier protein had a negligible effect on EPO accumulation, which the authors explain by a potential toxicity of the EPO-ELP fusion to the plant [76,79]. This finding is also in contradiction with the potent enhancing effect of fusion to ELP on the expression of human IL-10 and murine IL-4 [80], spider silk protein [80,81], full-size anti-HIV-1 antibody 2F5 [82] in tobacco leaves, and single-chain variable The average of four determinations is shown.…”
Section: Fig 11contrasting
confidence: 99%
“…When expressed by transgenic Physcomitrella patens lines, EPO was secreted through cell wall into culture medium and over 6 days, accumulated approximately 250 mg/g dry weight of moss [75]. In transgenic tobacco plants, high-level expression of non-fused human EPO containing its native signal peptide has been shown to affect plant morphology, causing retarded vegetative growth and male sterility [76]. However, by modifying the tobacco transformation system (eg, reducing cytokinin 6-BA concentration and changing a strain of Agrobacterium) and the expression cassette (flanking the EPO gene with the His tag and KDEL sequences), Musa et al [77] have developed transgenic tobacco overexpressing EPO with no plant health abnormality.…”
Section: Fig 11mentioning
confidence: 99%
“…For example, constitutive expression of the human epo gene affects vegelarive growth and male sterility of transgenic tobacco (Cheon et al, 2004). In our study, few AP-transformed plants bore seeds, suggesting that high constitutive hGM-CSF expression during early seed development may have harmed fertility.…”
Section: Discuss|onmentioning
confidence: 62%
“…Recently developed plant biotechnology offers additional advantages in production scale, economy, product safety, and ways of delivery (1)(2)(3)(4)(5)(6). At present, the main goal is to increase the overall expression yield of functional plant-derived proteins, especially those of viral origin, which sometimes seriously impair transgenic plant growth and development (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%